Synthesis of latex-antigen complexes from single and multiepitope recombinant proteins. Application in immunoagglutination assays for the diagnosis of Trypanosoma cruzi infection - Garcia, Valeria Soledad (2013)
The physical adsorption and the chemical coupling of recombinant proteins of Trypanosoma cruzi onto polystyrene and core-shell carboxylated particles were respectively investigated with the ultimate aim of producing latex-protein complexes to be used in an immunoagglutination assay able to detect the Chagas disease. To this effect, two single proteins (RP1 and RP5) and a multiepitope protein derived from three antigenic peptides (CP2) were evaluated, and sensitizations were carried out at different pHs. The maximum physical adsorption was produced at pHs close to the protein isoelectric point (i.e., pH 6 for RP5 and pH 5 for RP1 and CP2). High fractions of antigens were chemically bound to the carboxyl groups, and the highest surface density of linked protein was also observed at pHs close to the protein isoelectric point. The three latex-protein complexes obtained by covalent coupling at such pHs were tested with sera from a panel of 16 infected and 16 non-infected patients. In the immunoagglutination assays, the latex-CP2 complex produced the best discrimination between positive and negative sera.